Propagation of blackberry cultivars in three in vitro culture systems and evaluation of genetic uniformity - Doina Clapa; Monica Hârța; Mirela Cordea (Journal of Central European Agriculture)
The present study aimed to evaluate the influence of three in vitro culture systems: solid (SM), semi-solid (SSM), and liquid (temporary immersion system-TIS) on the number and quality of proliferated blackberry shoots, along with the analysis of genetic uniformity among the regenerated shoots. The following blackberry cultivars were tested: 'Čačanska Bestrna', 'Chester Thornless', 'Driscoll's Victoria', 'Karaka Black', 'Loch Ness', and 'Polar'. The culture medium used was Murashige and Skoog (MS), with 0.5 mg/L 6-Benzyladenine (BA). SM was gelled with 5 g/L plant agar; for SSM, wheat starch was used at 50 g/L (w/v), and a Platform bioreactor was used for TIS. The results revealed that, for all varieties, the highest number of shoots per initial inoculum was obtained in TIS, with the 'Karaka Black' variety presenting a maximum of 93.90±4.01. Considering the length of the proliferated shoots, all tested cultivars showed remarkable results in the SSM culture system gelatinized with 50 g/L wheat starch. The highest shoot length values were observed in 'Čačanska Bestrna', with values of 6.89±0.52 cm, followed by 'Chester' with 5.57±0.28 cm and 'Loch Ness' with 5.36±0.76 cm, respectively. The genetic uniformity of proliferated shoots was evaluated by start codon targeted (SCoT) markers.